Large-N Pion-Pion scattering, finite temperature effects and chiral symmetry restoration (2017)
The main focus of this thesis is to study QCD vacuum phenomena such as Chiral Symmetry Restoration (CSR) and generation of Bound States and Resonances; we attain this by analyzing two large N QCD-like models such as the nonlinear sigma model for a large number of flavors, and AdS/QCD nonconformal approaches where a large number of color is considered. We use the first model to study CSR after breaking it both dynamically and explicitly so that finite-temperature effects are easily introduced. We find some interesting properties regarding critical phenomena and universality classes. The second model we use allows to find the masses of light meson resonances in a gravitational-like approach defined at zero temperature (without Chiral Symmetry Breaking effects). We find here some interesting results since most of these masses are in great concordance with both experimental and theoretical/phenomenological results.--Tomado del Formato de Documento de Grado.